Gus Miftah’s Contemporary Da'wah Rhetoric Style on the Iced Tea Seller from Communication and Legal Perspectives: A Case Study - Fikriyah, Durrotul; Dwi Ratna Cinthya Dewi; Amri (Universitas Kristen Cipta Wacana, 2024)
The current study aims to examine the Contemporary Da'wah Rhetoric of Gus Miftah's preaching. However, the focus of this research is on the case of Gus Miftah and the Iced Tea Seller which went viral because Gus Miftah used impolite and offensive words in his preaching. The method used in this journal is Normative Law Research using a statutory approach. The results of this research are 1. The rhetoric of Da'wah in Islam does not only focus on the way of speaking, but also on morals and sincerity in preaching. 2. So far, Gus Miftah, in his preaching method, often uses jokes and impolite words, because the target of Gus Miftah's initial preaching was towards marginalized people, which then carried over to the stage where he lectured. 3. From a legal perspective, speaking or preaching using impolite words can be caught in the Law on Defamation or Insults in accordance with Article 310 of the Criminal Code if it is intended to insult you, but in the case of Gus Miftah and the Ice Tea Seller this is not included in the Law. This was invited because what Gus Miftah said was actually a joke, not an insult. Meanwhile, from the Communication Science perspective, what Gus Miftah said was very unethical for a preacher to say.